PENGARUH KOMUNIKASI WORD OF MOUTH DAN PREFERENSI KELUARGA TERHADAP KEPUTUSAN MAHASISWA MEMILIH PERGURUAN TINGGI SWASTA DI PROVINSI NUSA TENGGARA BARAT - Amiruddin Kalbuadi; Agus Hermanto; Lale Puspita Kembang; Rian Indranopa; Farha Farha (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to see the effect of word of mouth communication and family preferences in students' decisions to choose private universities in West Nusa Tenggara Province. The research was conducted by collecting data using Google Form and Paper Base media to respondents whose criteria had been determined using the purposive sampling method. The number of respondents used amounted to 105 students. This study uses multiple linear regression analysis and hypothesis testing using t test and F test. The feasibility test of the model uses the classical assumption test. The results of the analysis and hypothesis testing indicate that word of mouth and family preferences have a partial effect on students' decisions to choose private universities in West Nusa Tenggara Province. In the simultaneous test using the F test, word of mouth and family preferences affect students' decisions to choose private universities in West Nusa Tenggara Province.